Chromosomal assignment of centromere-specific histone CENH3 genes in rye (Secale cereale L.) and their phylogeny - Lipikhina, Yulia A. (Comp Cytogenet, 2017)
Abstract. Centromeres are essential for correct chromosome segregation during cell division and are determined by the presence of centromere-specific histone 3 (CENH3). Most of the diploid plant species, in which the structure and copy number of CENH3 genes have been determined, have this gene as a singleton; however, some cereal species in the tribe Triticeae have been found to have CENH3 in two variants. In this work, using the set of the wheat-rye addition lines we wanted to establish the chromosomal assignment of the CENH3 genes in the cultivated rye, Secale cereale (Linnaeus, 1753), in order to expand our knowledge about synteny conservation in the most important cereal species and about their chromosome evolution. To this end, we have also analyzed data in available genome sequencing databases. As a result, the αCENH3 and βCENH3 forms have been assigned to rye chromosomes 1R and 6R: specifically, the commonest variants αCENH3v1 and βCENH3v1 to chromosome 1R, and the rare variants, αCENH3v2 and probably βCENH3v2, to chromosome 6R. No other CENH3 variants have been found by analysis of the rye genome sequencing databases. Our chromosomal assignment of CENH3 in rye has been found to be the same as that in barley, suggesting that both main forms of CENH3 appeared in a Triticeae species before the barley and wheatrye lineages split.